Coherent spin control by electrical manipulation of the magnetic anisotropy. - George, R; Edwards, J; Ardavan, A (2013)
High-spin paramagnetic manganese defects in polar piezoelectric zinc oxide exhibit a simple, almost axial anisotropy and phase coherence times of the order of a millisecond at low temperatures. The anisotropy energy is tunable using an externally applied electric field. This can be used to control electrically the phase of spin superpositions and to drive spin transitions with resonant microwave electric fields.